(3GdEMcGe aj GNJUGQ CUhd GdCMcGes - (3CMeO Hf eMeO Hf MfHd, CHh YHO Gddg, GdTjHGfqj GdhGFdj,J (B241 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG eNJUQ ai kCUhd Gdabg s
(3BNQgG (B:s
(3hbO MUd HgPG HjGf GdQLMGf ef LgI GdbQGFf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B96s
Keywords: (3CUhd Gdabgs